Analisis Nilai Velocity Encoding terhadap Informasi Citra Magnetic Resonance Venography pada Penderita Tumor Kepala - Zita Hadiah Pratami; Sudiyono Sudiyono; Yeti Kartikasari (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: Brain Magnetic Resonance Venography (MRV) is a MRI examination of veins without contrast media. Phase Contrast (PC) MRV sequences uses phase shift protons that flow along the magnetic gradient into needed area (Field Of View).  PC MRV sequences use bipolar gradient to compensate the proton spin speed by adjusting the amplitude. The study aims to determine the Velocity encoding Value (VENC) to MRV image information on brain tumor patient and to determine the best image information through a technic to visualize the veins in brain tumor patient.Methods: This study was a quantitative study with quasi experimental approach. Data were collected in Radiology Department of Dr. Moewardi Surakarta Hospital on May to June 2016. Data was collected using questionnaire filled by three respondents. Data were analyzed statiscally using Friedman test and Wilcoxon test to determine the difference of value of Velocity Encoding (VENC) between 10 cm/sec, 15 cm/sec, 20 cm/sec, as well the mean rank test used to find out the best image information.Results: The statistical test showed that there were significant differences in image information of MRV, between VENC 10 cm/sec, 15 cm/sec and 20 cm/sec with p value was 0.032 (p˂0,05). The best result of MRV image information was when VENC value of 20 cm/sec used, indicated by the mean rank which was 2.83.Conclusion: There were significant differences of MRV image information between VENC 10 cm/sec, 15 cm/sec and 20 cm/sec. The best result of MRV image information was when VENC value of 20 cm/sec used, to visualize better anatomy of the veins, so that the presence of tumor thrombus in the veins can be ensured.